A newborn with ring chromosome 10, aganglionic megacolon, and renal hypoplasia. Issue 10 (October 1994) - Calabrese, G; Franchi, P G; Stuppia, L; Mingarelli, R; Rossi, C; Ramenghi, L; Marino, M; Morizio, E; Peila, R; Antonucci, A
Abstract : A newborn infant is reported who had aganglionic megacolon, renal hypoplasia, severe growth retardation, generalised hypotonia, and various dysmorphic features. Chromosome analysis of lymphocytes and fibroblasts showed a ring chromosome 10 with breakpoints at p13-15 and q26. AluI digestion showed that the ring chromosome was monocentric. FISH with an alpha satellite probe specific for chromosome 10 showed one signal only in about 20% of interphase nuclei. It is suggested that aganglionic megacolon could result from dynamic somatic mosaicism owing to loss of the ring chromosome.